Searching for spatial data resources by fitness for use - Ivanova, Ivana; Morales, J.; de By, R.; Beshe, T.; Gebresilassie, M. (Taylor & Francis Asia Pacific (Singapore), 2013)
During the search for spatial data resources, users, both experts and non-experts in the geoinformation field, are expected to know what type of spatial data resource they need, and in which clearinghouse or geoportal to search. In the case of success, they are still left with the decision on fitness for use, based on complex metadata, for the few cases where such metadata exists. To aid the search for spatial data resources, we propose a system for guided search for spatial data resources called GUESS. This system enhances current search engines with decision intelligence on fitness for use. GUESS works with profiles that contain data about users and about spatial data resources. From a free-form search request, GUESS identifies the spatial extent and the application domain, and searches for spatial data resources that comply with quality requirements in that domain. As a result, GUESS recommends a spatial data resource that best fits the user's needs. We illustrate capabilities of the proposed system on a request by a fictional user of a spatial data resource that is frequently present in the geoinformation world. © 2013 Copyright Surveying and Spatial Sciences Institute and Mapping Sciences Institute, Australia.